Therapeutic vaccines targeting HPV epitopes in human papillomavirus – positive oropharyngeal cancer: a critical review - Rossi, Giovanna; Tartaglia, Francesco Carlo; Denaro, Nerina; Ghidini, Michele; Goker, Funda; Garrone, Ornella; Giannì, Aldo Bruno; Del Fabbro, Massimo; Tartaglia, Gianluca Martino; Bossi, Paolo; Paderno, Alberto (Frontiers in Immunology, 2026)
Human papillomavirus-positive (HPV+) oropharyngeal squamous cell carcinoma (OPSCC) is a peculiar entity, with distinct patient, tumor, and biological characteristics, and a different prognosis compared to HPV-negative (HPV-) OPSCC. Due to the rising incidence, there is a need to develop novel therapeutic approaches, especially considering the long-term morbidities of traditional treatments such as surgery and chemoradiotherapy. In this regard, therapeutic vaccines targeting HPV epitopes have been put at the forefront of the immunotherapeutic strategies for HPV+ OPSCC. Multiple clinical trials are investigating their efficacy and safety in the advanced setting, more frequently as a combination therapy. As for the early setting, HPV therapeutic vaccines could represent a strategy to further deepen responses and to facilitate de-escalation of standard treatment. This review aims to provide the clinician with useful and up-to-date information on the current advances in this field. To that end, we will provide the results of the main ongoing/completed clinical trials including patients with OPSCC, focusing on immunogenicity and clinical benefit, in both early and advanced setting. We will also map the challenges and limitations in this area to guide future research.